Effects of Culture on the Balance Between Mathematics Achievement and Subjective Wellbeing - Meng, Jingyi; Liu, Simiao (Frontiers in Psychology, 2022)
Previous studies suggested that culture have impact on students’ mathematics achievement and subjective well-being, but few investigated the effects of culture on the balance between them. Drawing on Hofstede’s cultural dimensions theory, this study investigated the effects of culture on balance between students’ mathematics achievement and subjective well-being. Results showed the significant effects of cultural dimensions of long-term orientation vs. short-term orientation and indulgence vs. restraint. Students from countries of high long-term orientation and low indulgence culture were more likely to get both high mathematics achievement and high SWB. Besides, wealth-related variables (family SES and GDP per capita) and gender were also found to influence the odds ratio of balance. The findings confirmed the effects of national culture on the balance between mathematics achievement and SWB. Based on the findings, this study discussed the effects of long-term orientation and restraint culture and Confucian heritage culture's potential benefit. The results indicate that mathematics educators should consider cultural differences in educational practice and stress the importance and meaning of mathematics learning.